Efektifitas Aplikasi Pendaftaran Rawat Jalan Si Palui Terhadap Produktivitas Petugas Registrasi UPT Puskesmas Martapura 1 Kabupaten Banjar - Nisa, Khairun; Yunita, Nirma (Jurnal Kesehatan Indonesia, 2024)
The quality of service based on the outpatient registration application has been implemented by the Martapura 1 Health Center since 2019 and this is a technological innovation developed to simplify health services at the health center. So the operation of the Palui outpatient registration application should be carried out as closely as possible by the registration officer. However, in fact, the officers who act as admins controlling the operation of the application are deemed not to have the qualifications, one of which is that all non-medical recording officers, their responsiveness and concern for the operation of the Si Palui outpatient registration application are considered to be less than optimal. The aim of this research is to find out more deeply about the effectiveness of the Si Palui outpatient registration application on the productivity of UPT registration officers at Martapura 1 Health Center, Banjar Regency. This research is descriptive research with a qualitative approach. The number of samples was 4 people consisting of the Head of Medical Records and Outpatient Registration Staff. The results of the research are that the effectiveness of the outpatient registration application at Palui UPT Puskesmas Martapura 1 in terms of the aspects of achieving goals, integration and adaptation is included in the fulfilled category because it makes it easier for people to register for outpatient care. The productivity of registration officers on average falls into the High Productivity category of UPT Puskesmas Martapura 1. In conclusion, there is a link between the effectiveness of the Si Palui outpatient registration application and the productivity of UPT registration officers at Puskesmas Martapura 1.